The Influence of Environmental Performance and Environmental Costs on Financial Performance - Andre Alamsyah Ismail (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The purpose of this study was to examine the influence of environmental performance and environmental costs on financial performance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX), which publish financial reports and are listed in the Company Performance Rating Program in Environmental Management (PROPER) in 2015-2019. To take data samples in this study researchers used the purposive sampling method and obtained 140 data samples. The research method used is the verification method with a quantitative approach. Hypothesis testing is done using multiple linear regression analyses. The results showed that environmental performance has a positive influence on financial performance and environmental costs has a negative influence on financial performance.